Better Outcomes with a new Type of Pressure Wound Therapy for Mediastinitis after Cardiac Surgery - Deniz, Hayati; Arslanoglu, Yavuz; Ari, Murat (Progress in Nutrition, 2021)
Background: The aim of the present study is to compare the clinical outcomes and survival in our 40 patients underwent NPWT with or without instillation treatment for mediastinitis after cardiac surgery.Materials end Methods: In this study, we retrospectively compared the clinical outcome and survival in 40 patients undergoing VAC therapy with or without instillation treatment for DSWI after cardiac surgery. Only patients with mediastinitis those are consisting of sternum and presternal tissue infection after coronary bypass surgery were included in the present study.Results: Mean age of patients was 58.86 ± 11.6 and 57 patients of them were female and 33 of them were male. Primary surgery among the 40 patients presenting with DSWI; was coronary artery bypass revascularization. Conclusion: The use of VAC therapy with instillation has changed the management of complicated infected or colonized wounds and has become the standard of care our facility.